2000
DOI: 10.1080/003655200750023624
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Interferon-Alpha plus Ursodeoxycholic Acid versus Interferon plus Placebo in Patients with Chronic Hepatitis C Resistant to Interferon

Abstract: An IFN plus UDCA combination is more effective than IFN alone in terms of ALAT but not in terms of the virologic response. These results favor the hypothesis that UDCA has an effect on the biochemical indices of cellular injury independent of a change in primary bile acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Decreases serum ALT activity without affecting serum HCV RNA in chronic hepatitis C patients [98] Combination therapy with IFN did not lead to a significant increase in sustained responses compared with IFN alone [78,99] N-acetyl-l-cysteine (NAC) Glutathione (GSH) deficiency is associated with impaired T-cell function and impaired survival in some viral infections, such as HIV. NAC is used to replenish GSH [100] Patients with chronic hepatitis C are unlikely to benefit from the addition of NAC to conventional IFN [101] Ursodeoxycholic acid (UDCA) Serum liver enzymes improve in patients with HCV-related chronic liver disease during UDCA therapy [102] IFN/UDCA combination is more effective than IFN alone in terms of biochemical but not virological responses [103]…”
Section: Resultsmentioning
confidence: 99%
“…Decreases serum ALT activity without affecting serum HCV RNA in chronic hepatitis C patients [98] Combination therapy with IFN did not lead to a significant increase in sustained responses compared with IFN alone [78,99] N-acetyl-l-cysteine (NAC) Glutathione (GSH) deficiency is associated with impaired T-cell function and impaired survival in some viral infections, such as HIV. NAC is used to replenish GSH [100] Patients with chronic hepatitis C are unlikely to benefit from the addition of NAC to conventional IFN [101] Ursodeoxycholic acid (UDCA) Serum liver enzymes improve in patients with HCV-related chronic liver disease during UDCA therapy [102] IFN/UDCA combination is more effective than IFN alone in terms of biochemical but not virological responses [103]…”
Section: Resultsmentioning
confidence: 99%
“…2). The absence of lowering effect of UDCA on the endogenous bile acids has already been observed in patients with chronic hepatitis C. 22 Most importantly, a third explanation could be that the dosage regimen of UDCA was totally unadapted to the liver function of our patients. UDCA is exclusively metabolized and eliminated by the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Data on the use of ursodeoxycholic acid in hepatitis C are limited to a small number of trials done in the early 1990s [47]. These data indicated that ursodeoxycholic acid used by itself or in combination with interferon improved aminotransferase levels but had no beneficial effect on histology or HCV RNA titers.…”
Section: Hepatoprotectantsmentioning
confidence: 93%